1969
DOI: 10.1021/j100723a038
|View full text |Cite
|
Sign up to set email alerts
|

Infrared study of the adsorption and mechanism of surface reactions of 1-propanol on .gamma.-alumina and .gamma.-alumina doped with sodium hydroxide and chromium oxide

Abstract: involves the separation of repulsive charges as well as the migration of a very mobile proton, we are not surprised that fci = 1.4 X 106 sec-1 for this reaction is a great deal larger than the 25°first-order rate constant hi* ~10""5 to 10~8 sec-1 reported24 for the much studied reaction fcl* Cr(H20)es+--> Cr(H20)53+ + H20 that bears it a superficial resemblance. The iondipole attractive interaction in this latter reaction as well as the lower mobility of H20 than H+ could account for a markedly lower ki* than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…It was reported that the formation of hydroxyl compounds easily occurs on the surface of Pd/Al 2 O 3 due to its hydrophilic nature. The complete removal of the surface hydration requires temperatures as high as 900 °C under atmospheric pressure. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the formation of hydroxyl compounds easily occurs on the surface of Pd/Al 2 O 3 due to its hydrophilic nature. The complete removal of the surface hydration requires temperatures as high as 900 °C under atmospheric pressure. , …”
Section: Resultsmentioning
confidence: 99%
“…The complete removal of the surface hydration requires temperatures as high as 900 °C under atmospheric pressure. 35,36 Table 1 also shows the textural properties of pristine, watersoaked, and sulfur-treated Pd/SOMS. The BET surface area, BJH pore volume, and BJH pore diameter of pristine Pd/ SOMS were found to be 590 m 2 /g, 0.73 cm 3 /g, and 3.9 nm, respectively.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…In flash desorption28•6 an adsorbate is allowed to accumulate to a desired coverage n0 on the surface maintained at a temperature T0, and then the desorption rate parameters are determined by measuring the amount desorbed as a function of time by programming the surface temperature to vary approximately as T -To 4ft where ß is a constant. The desorption rate from, a single state is given by the expression = vo{m)e-F-*>'RTnm (1) df where r0(m) is the preexponential factor for desorption with order m, and Ed is the activation energy of desorption. For high pumping speeds one obtains a peak for each binding state, and by analysis of the position and shape of these peaks the parameters vB, Ed, to, and n0 for each state can be obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that the surface species formed by other product species, such as 1-PO, 2-PO or ethanol, also exhibit (CH 3 ) and (CH 2 ) bands with nearly identical frequencies [38][39][40], it is reasonable to think that they could correspond to 1,2-PDO, since it is the major product in the reaction (30.6 and 36.1% selectivity for the experiments with 15 and 30 wt% initial glycerol concentrations). In addition, the higher number of OH groups of 1,2-PDO makes its adsorption on the catalyst surface easier [37], as it was explained above.…”
Section: In-situ Atr-ir Studies Of Glycerol Hydrogenolysismentioning
confidence: 99%